EFEKTIVITAS PEMBELAJARAN BAHASA ARAB MENGGUNAKAN METODE ELEKTIK PADA SISWA KELAS 3 SDIT NUUR ALAA NUUR - Salsabila, Luthfiyah; Hendra, Faisal (CV. Lafadz Jaya, 2024)
The right method is very important in learning activities, especially in learning Arabic. The lack of understanding of students in receiving learning is a sign of the problem of inappropriate learning methods and factors of diverse brain development of children. This study aims to determine the effectiveness of Arabic language learning using the electic method as well as connecting the evaluation results with the brain abilities of girls and boys. The data was taken from the 3rd grade students of SDIT Nuur Alaa Nuur totaling 66 students, and supporting data from the Arabic language teacher in the class. The method used in this research is qualitative and observation techniques with the aim of obtaining data according to field facts. From the results of calculations and analysis, it is found that the effectiveness of 3rd grade Arabic learning at SDIT Nuur Alaa Nuur is quite good, the percentage of student results who get scores of 70-79 is not more than 10%. Then the results of the evaluation scores can be concluded that the language acquisition ability of female students is superior to male students. Arabic Language Learning, Electical Method, Language Acquisition